LAND TENURE TRANSFORMATION IN A REMOTE ISLANDS: A case of a historical sociology prespective in Karimunjawa islands - Yety Rochwulaningsih (JOURNAL OF COASTAL DEVELOPMENT, 2011)
The interesting problem is the phenomenon of the transformation of land tenure of local residents to the outside residence massively. The research method used is a qualitative method by using data collection techniques of depth interviews, group interviews, participant observation, archival studies and documents and literature study. The results showed, that there has been a transformation of land tenure with the indicator of controlling the small islands in Karimunjawa Islands by outside residents. Of the 22 small islands with a total area of 358.9 ha of which are not inhabited by the population, remained 24 ha (6.69%) is controlled by local residents. The condition is caused by several factors, among others: (1) enactment Karimunjawa as a National Marine Park, and then as one of the leading tourism region of Central Java province, (2) the low level of education of local residents and the limited productive business opportunity in agricultural sector, (3) low levels of welfare and the weak bond of local residence to their land property. In this context the land then becomes a commodity more than the means of production, and a decline in social status of the local population, which is only switched on as a tenant or other livelihood as laborers or open a small business.